Association of Race and Major Adverse Cardiac Events (MACE): The Atherosclerosis Risk in Communities (ARIC) Cohort - Ericha G Franey; Donna Kritz-Silverstein; Erin L Richard; John E Alcaraz; Caroline M Nievergelt; Richard A Shaffer; Vibha Bhatnagar (Journal of Aging Research)
Background and Aims. To evaluate the association of self-reported race with major adverse cardiac events (MACE) and modification of this association by paraoxonase gene (PON1, PON2, and PON3) single nucleotide polymorphisms (SNPs). Methods. Included in this longitudinal study were 12,770 black or white participants from the Atherosclerosis Risk in Communities (ARIC) cohort who completed a baseline visit (1987–1989) with PON genotyping. Demographic, behavioral, and health information was obtained at baseline. MACE was defined as first occurrence of myocardial infarction, stroke, or CHD-related death through 2004. Cox proportional hazards regression was used to evaluate the association between race and MACE after adjustment for age, gender, and other demographic and cardiovascular risk factors such as diabetes and hypertension. Modification of the association between PON SNPs and MACE was also assessed. Results. Blacks comprised 24.6% of the ARIC cohort; overall, 14.0% of participants developed MACE. Compared with whites, blacks had 1.24 times greater hazard of MACE (OR = 1.24,95%CI = 1.10,1.39) than whites after adjusting for age, gender, BMI, cigarette and alcohol use, educational and marital status, and aspirin use. This association became nonsignificant after further adjustment for high cholesterol, diabetes, and hypertension. None of the evaluated SNPs met the significance level (p<0.001) after Bonferroni correction for multiple comparisons. Conclusions. No association between race and MACE was identified after adjusting for high cholesterol, diabetes, and hypertension, suggesting that comorbidities are major determinants of MACE; medical intervention with focus on lifestyle and health management could ameliorate the development of MACE. Further studies are needed to confirm this observation.